'I WILL INTERPRET': THE EIGHTH LETTER AS A RESPONSE TO PLATO'S LITERARY METHOD AND POLITICAL THOUGHT. (December 2019) - Atack, Carol
Abstract : This paper explores the political thought and literary devices contained in the pseudo-Platonic Eighth Letter, treating it as a later response to the political thought and literary style of Plato, particularly the exploration of the mixed constitution and the mechanisms for the restraint of monarchical power contained in the Laws . It examines the specific historical problems of this letter, and works through its supposed Sicilian context, its narrator's assessment of the situation, and the lengthy prosopopoeia of the dead Syracusan politician Dion, before concluding with a consideration of its contribution to our knowledge of Greek political thought after Plato.